Baso model-based strategic planning training impact on rural mosque effectiveness at FELDA settlement Malaysia / Mohamed Zakaria Mohamed Yahya - Mohamed Yahya, Mohamed Zakaria (Institute of Graduate Studies, UiTM, 2018)
The effects of globalisation have resulted in many non-profit organisations (NPOs) especially the rural mosque institutions need to transform and exploring beyond their historical lock-in weather at the national boundaries or global in search of a better organisational effectiveness. Preliminary study in 2015 by FELDA mosque auditor-team showed that mosque functions turn to be less effective. Earlier in 1994, UMMI Foundation under the Prime Minister Office (PMO) study found that mosque functions turn to be less effective and eroded. In 2015 FELDA Management team take an initiative to improve FELDA Settlement mosques effectiveness by used the BASO Model-based strategic planning training intervention on the 160 mosque leaders from four selected mosques. The objectives of this study are to examine the impact of BASO Model-Based Strategic Planning Training (as independent variable) and Training Follow up Sessions (as mediating variable) towards FELDA Mosque effectiveness. This research also examined the effect of transformational leadership as moderating factor towards mosque organisational effectiveness. This present research applied quasiexperimental approach to measure the impact of this intervention towards mosque leaders attitude, knowledge and skills. This longitudinal research consists of four time-line of pre-test and post-test data collection in the total duration of six months. This study findings provide empirical evidence to explained positive or negative impact of this BASO Model-Based Strategic Planning Training intervention. There are six main objectives, six research questions, twenty-four direct relationships tested to support variables used in this study research framework and forty-nine hypotheses analysed in order to achieve the research aims…